2020
DOI: 10.1111/jfb.14608
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in inhibitory motor control in guppies, Poecilia reticulata

Abstract: Inhibitory control (IC) is the ability to overcome impulsive or prepotent but ineffective responses in favour of more appropriate behaviours. The ability to inhibit internal predispositions or external temptations is vital in coping with a complex and variable world. Traditionally viewed as cognitively demanding and a main component of executive functioning and self‐control, IC was historically examined in only a few species of birds and mammals but recently a number of studies has shown that a much wider rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…We tested the presence of a socially-mediated plasticity in inhibitory control in the guppy fish, Poecilia reticulata. In this species, several studies have reported refined inhibitory abilities Santacà et al, 2019) and remarkable intraspecific variability in cognition (reviewed in , including in inhibitory control (Macario et al, 2021;Savaşçı et al, 2021). Furthermore, variation in social environment has been consistently reported in natural guppy populations (Darden et al, 2020;Edenbrow et al, 2011;Magurran & Seghers, 1990, Seghers & Magurran, 1991Seghers & Magurran, 1991).…”
Section: Introductionmentioning
confidence: 91%
“…We tested the presence of a socially-mediated plasticity in inhibitory control in the guppy fish, Poecilia reticulata. In this species, several studies have reported refined inhibitory abilities Santacà et al, 2019) and remarkable intraspecific variability in cognition (reviewed in , including in inhibitory control (Macario et al, 2021;Savaşçı et al, 2021). Furthermore, variation in social environment has been consistently reported in natural guppy populations (Darden et al, 2020;Edenbrow et al, 2011;Magurran & Seghers, 1990, Seghers & Magurran, 1991Seghers & Magurran, 1991).…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, not all studies find consistency in behaviours affected by inhibitory control. For example, studies which investigate consistency in how inhibitory control affects performance across tasks tend to find no consistency, potentially because these tasks measure different aspects of inhibitory control (reviewed in Macario et al 2020). Consistency in inhibitory control in other studies may also be affected by learning, with repeated experience of a task individuals have been found to demonstrate better inhibitory control (e.g., Kabadayi et al 2018;Ryding et al 2021;van Horik et al 2018), or length of time between experiences of the task.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not know yet how inhibitory control is affected by selection. To begin with, little is known about temporal consistency in behaviours influenced by inhibitory control (but see, Kabadayi et al 2018;Macario et al 2020;Ryding et al 2021;van Horik et al 2018), nor how these behaviours correlate with each other. Behaviours influenced by inhibitory control include impulsive behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…If much of the presumably intelligence spatial navigation tasks can be performed by animals without VTE, then what is the benefit of VTE? Some suggestive evidence can be seen in the superior performance of mammals on certain tasks requiring “hard choices.” For example, mammals tend to substantially outperform non-mammal vertebrates on detour tasks, where an animal has to make a roundabout path around a barrier in order to get to a goal (MacLean et al, 2014 ; Gatto et al, 2018 ; Macario et al, 2020 ). Mammals also seem to outperform non-mammals in delayed gratification tasks, whereby they have to resist choosing an immediate small reward in order to get a delayed larger reward (Stevens et al, 2010 ).…”
Section: Evidence For the Modelmentioning
confidence: 99%